The role of horizontal gene transfer in Staphylococcus aureus host adaptation - Guinane, Caitriona M.; Penadés, José R.; Fitzgerald, J. Ross (Taylor & Francis, 2020)
Staphylococcus aureus is an important human pathogen that also causes economically important infections of livestock. In a recent paper, we employed a population genomic approach to investigate the molecular basis of ruminant host adaptation by S. aureus. The data suggest that the common pathogenic clone associated with small ruminants originated in humans but has since adapted to its adopted host through a combination of allelic diversification, gene loss and acquisition of mobile genetic elements. In particular, a new subfamily of staphylococcal pathogenicity islands (SaPI) was identified encoding a novel von Willebrand factor-binding protein (vWBP) with ruminant-specific coagulase activity. The wide distribution of vWBP-encoding SaPIs among ruminant strains implies an important role in hostadaptation. In the current article we summarize the findings of the paper and comment on the implications of the study for our understanding of the molecular basis of bacterial host adaptation